2022
DOI: 10.3989/redc.2022.4.1917
|View full text |Cite
|
Sign up to set email alerts
|

Indización automática de artículos científicos sobre Biblioteconomía y Documentación con SISA, KEA y MAUI

Abstract: Este artículo evalúa los sistemas de indización automática SISA (Automatic Indexing System), KEA (Keyphrase Extraction Algorithm) y MAUI (Multi-Purpose Automatic Topic Indexing) para averiguar cómo funcionan en relación con la indización realzada por especialistas. El algoritmo de SISA se basa en reglas sobre la posición de los términos en los diferentes componentes estructurales del documento, mientras que los algoritmos de KEA y MAUI se basan en el aprendizaje automático y las frecuencia estadística de los t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Table 1 shows an increase in the number of documents citing Tanzanian IR contents year after year for five years. Further, the study found that for the period of five years (2018 to 2022), SUA IR was the highly cited IR (46) with an average of 9.2 citing documents per year, and UDOM IR was the least cited IR (8) with an average of 1.6 citing documents per year. This is explained by the fact that the two repositories have different ages; SUA IR was established in 2014, while UDOM IR was established in 2019.…”
Section: Number Of Documents Indexed In Scopus Citing Tanzanian Ir Co...mentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 shows an increase in the number of documents citing Tanzanian IR contents year after year for five years. Further, the study found that for the period of five years (2018 to 2022), SUA IR was the highly cited IR (46) with an average of 9.2 citing documents per year, and UDOM IR was the least cited IR (8) with an average of 1.6 citing documents per year. This is explained by the fact that the two repositories have different ages; SUA IR was established in 2014, while UDOM IR was established in 2019.…”
Section: Number Of Documents Indexed In Scopus Citing Tanzanian Ir Co...mentioning
confidence: 99%
“…The literature indicates various concepts that have been covered related to measuring the impacts of institutional repositories. They include measuring IR impact (Ndhlovu, 2021;Wheeler et al, 2022); IR content document types (Arsyad et al, 2018;Hyland, 2017;Mozersky et al, 2021); documents citing IR contents (Demetres, Michelle, Delgado and Wright, 2020;Gil-Leiva et al, 2022;Koulikov, 2010;Rethlefsen et al, 2021); IR contents cited by documents indexed in reputable indexing databases (Ndhlovu, 2021;Wheeler et al, 2022) and authors affiliations (Bachelet et al, 2019;Hottenrott & Lawson, 2017;Ndhlovu, 2021;Wheeler et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation